MULTIDIMENSIONAL POVERTY IN T. S. ELLIOT’S MORNING AT THE WINDOW - Abdika Taslih Amrullah; Christinawati; Edi Dwi Riyanto (Universitas Negeri Surabaya, 2022)
Poverty is a phenomenon of human suffering that is often brought up as the main theme in the works of literature. The study examines how poverty is manifested in the poem entitled Morning at the Window by T. S. Elliot. The analysis focuses on interpreting the poem’s meaning and further analyses the portrayal of poverty. The theoretical framework used to analyze the poem's meaning is the semiotics of poetry by Michael Riffaterre. The dimensions of poverty by Robert Chambers are also used to analyze the elements of poverty that constructed the main issue of the poem. The analysis focuses on the unsustainability of meaning and interpretation from heuristic and hermeneutic reading. The overall meaning is drawn to reveal how the poem portrays the issue of poverty. Besides, the concept of poverty depicted in the poem is demystified based on the dimensions of poverty by Chambers. The analysis shows that the poem illustrates its main issue by strongly depending on the objective, representing poverty’s dimensions. The identified dimensions of poverty that constructed the issue are powerlessness, isolation, vulnerability, and poverty. These dimensions are illustrated by depicting the maids’ physical and mental state caused by living in poverty.